Penggunaan Media Dalam Pembelajaran PPKn di Prestige Bilingual School Kota Medan - Abdulgani Jamora Nasution; Jelita Dwi Septya; Fadhilah Uswah; Adinda Widyaningsih; Harri Gusnirwan (Fakultas Tarbiyah IAI Nasional Laa Rooiba, 2023)
Education is an action that is carried out consciously and planned which aims to change the behavior of everyone. Departing from the problem of the education curriculum, various activities in the world of education and learning actually found studies that must be critically discussed in order to achieve the ideal goals of education. One that cannot be underestimated is the use of learning media. Based on the explanation above, the researcher is interested in carrying out a study entitled